The Challenges in Managing Proliferative Diabetic Retinopathy with Neovascular Glaucoma - Putri A Idham; Elvioza Elvioza; Andi Arus Victor; Gitalisa Andayani; Ari Djatikusumo; Anggun Ramayudatha (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: The aim of this study is to emphasize the importance of close monitoring of the disease progression, minimize late complication, and knowing the important parameters of succesful treatment.Methods: A 52 years old woman with proliferative diabetic retinopathy was referred to Vitreoretina division. Patient came with chief complaint blurry vision of the left eye. Patien was diagnosed with diabetes melitus type 2 since 10 months ago. At ophthalmological examination, there was iris neovascularization on the left eye. Due to this finding, patient was given treatment for the proliferative diabetic retinopathy and neovascular glaucoma.Results: The patient undewent intravitreal injection of bevacizumab and Kehki Meta implant surgery after panretinal photocoagulation laser. Neovascularization of the iris was regressed and the intraocular pressure was controlled.Conclusion: This patient underwent laser panretinal photocoagulation, bevacizumab injection and Keiki Mehta implant surgery. The result was good. The neovascularization was regressed. Closed monitoring should be continued to evaluate the progression of the disease and control the intraocular pressure to prevent further visual loss.Â Keywords: Proliferative diabetic retinopathy, neovascular glaucoma, diabetic macular edema